PENGARUH UMUR BATANG BAWAH DAN TINGKAT PENAUNGAN PADA PENYAMBUNGAN BIBIT JARAK PAGAR (JATROPHA CURCAS L.) - Sugiatno, Sugiatno; Hamim, Herawati (JURNAL AGROTROPIKA, 2009)
To get high quality physic nut seedling one of effort is with vegetative propagation especially with grafting. The objective of this study was to evaluate the effect the maturity of rootstocks and shading rate on the effectiveness of grafting and the growth of seedling of Jatropka. The experiment was conducted in Labuhan Dalam, Subdistrict Tanjung Seneng, the City of Bandar Lampung from January-June 2008. Is a factorial experiment (3X4) with split plot design, shading degrees as main plot consisted without shading, light shading, moderate shading, and heavy shading. Root stock age as subplot consisted 6, 8, and 10 weeks after transplanting. The treatments were consisted 3 replication and each experiment unit consisted 10 seedlings. The result shows that root stock age 8 and 10 weeks produces physic nut seedling growth better than root stock age 6 week. Physic nut seedling without shading and light shading (1 layer paranet) grow better than with moderate shading (2 layers paranet) and heavy shading (3 layers paranet);Key words: Physic nut, root stock age, shading